Studying fatty acid content in red blood cell membranes in diabetic retinopathy of type 2 diabetes patients - Mykhailo Bykhovets (Kazimierz Wielki University, 2020)
Introduction. Studying pathogenetic pathways that are formed under conditions of hyperglycaemia and trigger further metabolic changes resulting in diabetes complications over time are of special interest both in theoretical and practical medicine. Membrane of the red blood cell that stays in blood constantly and relatively durable is an obvious participant of all metabolic changes and cannot but reflect changes in metabolism. Objective: to study content of fatty acids (FAs) in red blood cell membranes of patients with diabetic retinopathy (DR) with type 2 diabetes (T2D). Materials and methods. The study enrolled 73 subjects maximally matched by age and gender: 50 patients with established long-lasting T2D complicated with DR and 23 patients in the control group. All the biochemical tests were performed at the certified laboratory under the standard methods. Gas chromatography was applied to study FA spectrum. Statistical analysis was performed in IBM SPSS Statistics 23. Results and discussion. The key difference between the lipid metabolism of patients with complicated long-lasting T2D and healthy subjects was a significant difference in FA content redistribution in the red blood cell membranes represented by increased "saturation". The content of saturated FAs (SAFAs)in patients with DR was higher than in the CG: 1.5-fold for palmitic (С:16), 2-fold for myristic(С:14), pentadecanoic (С:15) and margaric (С:17) (Р < 0.05). The content of saturated stearic (С:18) FA was not changed significantly.The content of unsaturated FAs(USFAs) have changed multidirectionally: the content of linoleic (С18:2) and arachidonic (С20:4) decreased 1.5-1.7-fold, respectively. The content of linolenic (С18:3) increased 2-fold, and content of oleic FA (С18:1) was not changed significantly. Conclusion. Study of the fluctuations of FA levels in red blood cell membranesplays animportant role in the development of insulin resistance, T2D and its microvascular complicationsthat can be applied in creating treatment and prevention strategies ofDRin type 2 diabetes patients.